Investigaciones Europeas de dirección y economía de la empresa: Informe editorial - Manuel Guisado Tato; T. Crespo Franco (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2010)
The editorial process of Investigaciones Europeas de Dirección y Economía de la Empresa during 2009 is reported below. A total of 92 manuscripts were received, mainly from Spain (95,7%). Consequently, the language most frequently used in the manuscripts was Spanish, followed by Portuguese and English. The mean time between reception and publication of a manuscript was low (296 days). The rejection rate was 70,71%. In 2009, 34 original research articles were published.
Keywords: 330